IMPLEMENTASI SUPERVISI AKADEMIK DAN MANAJERIAL PADA MASA PANDEMI COVID-19 - Maisyarah Maisyarah (Balai Diklat Keagamaan Banjarmasin, 2021)
Abstract Madrasah supervisors have full authority and responsibility for their fostered madrasas. This study aims to determine the implementation of academic and managerial supervision at the target madrasas in connection with the Covid-19 pandemic outbreak. The research subjects consisted of 4 madrasah principals and 59 teachers. The data source is primary data, the data collection is carried out from August 2020 to March 2021. The object of research is academic supervision and managerial supervision. Data collection techniques through interviews, observations, hearings and document studies. As for the data analysis technique using descriptive statistics and quantitative descriptive. Results of qualified academic supervision Good and qualified managerial supervision Fair. Overall, the implementation of academic and managerial supervision at the target madrasas during the Covid-19 pandemic with sufficient qualifications. The head of the madrasa continues to strive to be able to carry out his duties with balance and obtain results as expected (at least Good). The results of this implementation serve as a basis, reference and follow-up for supervision in the following year.